Characteristics and Genesis of Mount Pengki: A Scoria Cone of Dago Volcano, West Java, Indonesia - Adimedha, Tyto Baskara; Ciputra, Roni Cahya; Rosianna, Ilsa; Sukadana, I Gde; Harijoko, Agung; Handini, Esti; Pratiwi, Fadiah; Indrastomo, Frederikus Dian; Syaeful, Heri; Rachael, Yoshi; Sukmawan, I Gusti Made (EKSPLORIUM, 2024)
Scoria cones are a typical product of volcanic activity constructed by the bomb and lapilli-sized pyroclasts formed by Strombolian eruption. Mount Pengki is a scoria cone found in Miocene Dago Volcano, West Java. Mount Pengki was a remnant of a Miocene volcano that was exceptionally well preserved and exposed. This scoria cone contains layers of scoria beds and a lava flow unit. The study aims to characterize the exposed scoria bed deposits and investigate the eruptive history and degradation process of Mount Pengki. Field observation, including measured sections and detailed characterizations of the Mount Pengki quarry, allows us to observe its volcanic sequence from its internal structure toward the surface. Morphometric analysis of Mount Pengki can describe the degradation process undergone by the scoria cone. The early phase deposits were characterized by massive to weakly bedded, poorly sorted, clast-supported beds mainly composed of coarse lapilli to bombs/blocks scoria grain. The middle phase deposit typically shows well-stratified, well-sorted, clast-supported scoria beds with coarse ash to coarse lapilli grain size. The late phase deposit is similar to the middle phase deposit, with additional features of coarser-grain, reverse grading, and clast-supported lenticular beds. Eruptive mechanisms involved in the formation of Mount Pengki include ballistic transport of clasts, fallout deposition, and grain avalanching process. The degradation process was likely influenced by prolonged exposure to weathering, cone rim collapse, and regional deformation processes.